PROFIL WAWASAN GURU SEKOLAH DASAR DALAM PEMBELAJARAN NUMERASI BERBASIS LEVEL KEMAMPUAN SISWA - Mohammad Archi Maulyda; Lalu Hamdian Affandi; Awal Nur Kholifatur Rosyidah; Itsna Oktaviyanti; Muhammad Erfan; Iwan Hamdani (IKIP Siliwangi, 2021)
This study aims to explore information related to the insight profile of elementary school teachers related to basic numeracy concepts based on learning according to the level where students are grouped according to their abilities. This study is a descriptive-qualitative study that describes the numerical insight profile of teachers from 6 elementary schools in Karang Sidemen Village, North Batukliang District, Central Lombok Regency, West Nusa Tenggara. The research activity was carried out in conjunction with the ‘Semua Anak CERDAS” training program for elementary school teachers in Karang Sidemen Village. The data collection process used numeracy test questions given to 30 research subjects. Each subject takes 1 topic which is discussed in depth regarding the concept of numeracy in learning based on students' abilities based on levels. Sub-aspects that become indicators of the teacher's numeracy insight profile include the components ‘Semua Anak CERDAS” approach, the scope of basic numeracy, grouping students based on basic numeracy skills, and the level of students' basic numeracy skills. The results showed that of the 30 teachers who took the numeracy test questions, only 6 teachers scored > 70. In addition, the schools studied with the lowest numeracy insight were SDN Rangkep and SDN Repok Sintung Barat.